2002
DOI: 10.1111/j.0014-3820.2002.tb01396.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Effects and the Potential for Evolution in a Natural Population of Animals

Abstract: Maternal effects are widespread and can have dramatic influences on evolutionary dynamics, but their genetic basis has been measured rarely in natural populations. We used cross-fostering techniques and a long-term study of a natural population of red squirrels, Tamiasciurus hudsonicus, to estimate both direct (heritability) and indirect (maternal) influences on the potential for evolution. Juvenile growth in both body mass and size had significant amounts of genetic variation (mass h(2) = 0.10; size h(2) = 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
99
2
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 127 publications
(109 citation statements)
references
References 33 publications
(36 reference statements)
7
99
2
1
Order By: Relevance
“…The model therefore included sex-specific dominance and maternal effects (McAdam et al, 2002;Wilson et al, 2010;Wolak and Keller, 2014) as random effects. Because we had several nest box choices for a fraction of individuals over the years, we accounted for a permanent environment effect by including the identities of the male and female as random effects.…”
Section: Animal Model At the Pair Level: Specification And Variance Pmentioning
confidence: 99%
“…The model therefore included sex-specific dominance and maternal effects (McAdam et al, 2002;Wilson et al, 2010;Wolak and Keller, 2014) as random effects. Because we had several nest box choices for a fraction of individuals over the years, we accounted for a permanent environment effect by including the identities of the male and female as random effects.…”
Section: Animal Model At the Pair Level: Specification And Variance Pmentioning
confidence: 99%
“…A variety of genetic, maternal and environmental factors can lead to variation among individuals within a population. For example, in the Kluane red squirrel population, it has been shown that the individual traits vary with territory quality (LaMontagne 2007), year of birth (Descamps et al 2008b) or characteristics of the mothers (McAdam et al 2002;Descamps et al 2008a) Such individual heterogeneity has to be accounted for when studying trade-offs and/or age-specific change in the life-history traits ( Vaupel & Yashin 1985;Cam et al 2002;Van de Pol & Verhulst 2006;Nussey et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…That is, in addition to producing too few offspring if litter size is reduced owing to high early mortality, monandrous females might also sometimes exceed optimal litter size, as a consequence of adopting a compensation strategy of increased ova production. This could also be costly because exceeding optimal litter size can have long-term fitness consequences both for offspring growth and survival, and/or female survival and future reproductive success (Aparicio 1993;Morris 1996;Sikes & Ylö nen 1998;Humphries & Boutin 2000;McAdam et al 2002;Réale et al 2003), although such costs may be avoided in species with paternal or communal care of offspring. Alternatively or additionally, increased variation in litter size associated with monandry might reflect ecological factors that were not considered in the present study (for example, Sikes 1998).…”
Section: Discussionmentioning
confidence: 99%